(untitled) (Research, Society and Development, 2022)
The purpose of this rehearsal is to investigate the curricular content of Capoeira in Physical Education courses: Possibilities and Strategies for Teaching, based on the Curricular Guidelines, Resolutions CNE/CP 01 and 02/2002 and 07/2004, regarding the process of education in Physical Education. To this end, we worked from the following perspectives: a historical analysis of capoeira in the world, unfolding in Brazil; professional training in Physical Education; Capoeira and its cultural aspects; capoeira as art and education; and the debate on trends in Physical Education. The goal was to identify how capoeira can be inserted into Physical Education courses. We concluded that there are few empirical studies regarding the results of the curricular content of capoeira in Physical Education courses under the current regulatory scenario, that there are margins for the choice of critical competencies in the professional training process involving capoeira. The conclusion is that the teachers are committed to the educational scenario, producing content on capoeira and passing it on to their students, in order to train new professionals and researchers in the field of Physical Education, as well as to make it possible to redeem this culture. We propose the development of a capoeira curriculum for Physical Education courses, making it possible to develop teaching strategies, and thus training professionals to act while incorporating this cultural redemption.